Identifying Important Ports in Maritime Silk Road Shipping Network from Local and Global Perspective. Issue 12 (December 2022) - Yang, Yanbin; Liu, Wei; Xu, Xu
Some key ports exist in the Maritime Silk Road shipping network that have a high impact on the whole of maritime transportation. An efficient identification of these crucial ports is of great importance, to alleviate the spread of port congestion, control shipping delays, and improve transportation efficiency. This paper proposes a novel method to identify the key ports by comprehensively considering local propagation and global centrality (LPGC), based on the complex network theory. Taking the ports along the Maritime Silk Road shipping network as an example, the Susceptible–Infected–Susceptible (SIS) model and Kendall's correlation coefficient are compared with several centrality measures to evaluate the feasibility and efficiency of the LPGC method. The obtained results demonstrate that, compared with the existing methods, the proposed method has higher accuracy and can more accurately identify the influential ports. Finally, the obtained port importance ranking also provides a theoretical basis for the selection of ports that should give a priority to maintaining or ensuring their service capacity in practice.